Bacillus velezensis tolerance to the induced oxidative stress in root colonization contributed by the two‐component regulatory system sensor ResE. (3rd May 2021) - Zhang, Huihui; Liu, Yunpeng; Wu, Gengwei; Dong, Xiaoyan; Xiong, Qin; Chen, Lin; Xu, Zhihui; Feng, Haichao; Zhang, Ruifu
Abstract: Efficient root colonization of plant growth‐promoting rhizobacteria is critical for their plant‐beneficial functions. However, the strategy to overcome plant immunity during root colonization is not well understood. In particular, how Bacillus strains cope with plant‐derived reactive oxygen species (ROS), which function as the first barrier of plant defence, is not clear. In the present study, we found that the homolog of flg22 in Bacillus velezensis SQR9 (flg22 SQR9 ) has 78.95% identity to the typical flg22 (flg22 P.s. ) and induces a significant oxidative burst in cucumber and Arabidopsis. In contrast to pathogenic or beneficial Pseudomonas, live B. velezensis SQR9 also induced an oxidative burst in cucumber. We further found that B. velezensis SQR9 tolerated higher H2 O2 levels than Pst DC3000, the pathogen that harbours the typical flg22, and that it possesses the ability to suppress the flg22‐induced oxidative burst, indicating that B. velezensis SQR9 may exploit a more efficient ROS tolerance system than DC3000. Further experimentation with mutagenesis of bacteria and Arabidopsis showed that the two‐component regulatory system, ResDE, in B. velezensis SQR9 is involved in tolerance to plant‐derived oxidative stress, thus contributing to root colonization. This study supports a further investigation of the interaction between beneficial rhizobacteria and plant immunity. Abstract : The beneficial rhizobacterium Bacillus velezensis SQR9 or its flg22 peptides triggered oxidative burst in cucumber and Arabidopsis . The two‐component regulatory system, ResDE, in B. velezensis SQR9 is involved in tolerance to plant‐derived oxidative stress, thus contributing to root colonization.